Youth and adult education and special education: the (re)invention of the necessary articulation between these areas - Clarissa Haas (Universidade Federal de Santa Maria, 2015)
This exploratory study proposes the approximation between Youth and Adult Education and Special Education, by analyzing the contributions provided by the national lawful and political guidance about Special Education considering the Inclusion Education perspective. The publications from the Youth and Adult Education Forums and the academic production have brought some dialogue between both areas. The theoretical and critical immersion in "places" considered as legitimate to make this dialogue possible from the premise of Youth and Adult Education being in the regular school as a potentialized space for impaired youths and adults to develop their singular ways of learning. This investigation has pointed out the scarcity of studies within this focus and the need for widening the discussion about the Specialized Education to impaired youths and adults.